(untitled) (Czech Journal of International Relations, 1967)
The Pugwash movement arose from the initiative of atomic scientists from various countries who realized their responsibility for human life. That is why they opposed the war and began to discuss how to reduce or even eliminate the threat of war. Since they could provide very valuable, sometimes even decisive information in various areas with their knowledge, they could significantly contribute to the conclusion of agreements banning nuclear weapons tests in the atmosphere right at the beginning of their activities. The initiators of the movement, grouped mainly in The Pugwash Standing Committee, however, were not satisfied with these results. They remained faithful principles they agreed upon at a meeting in a small village in the USA bearing the Indian name of Pugwash and continued their efforts to eliminate the outbreaks of war and dangers to world peace in all areas. The movement expanded considerably. Not only the leaders of nuclear research in the USA, USSR and Great Britain are among them, but also nuclear physicists from all important countries, scientists from a number of other disciplines, including social sciences.